2000
DOI: 10.1155/2000/697943
|View full text |Cite
|
Sign up to set email alerts
|

Peptic Disease in Elderly Patients

Abstract: The increase in life expectancy demands that more attention be given to gastrointestinal problems, such as peptic ulcer disease, in elderly people. This review summarizes many of the physiological changes that have a role in peptic ulcer disease in elderly patients. How Helicobacter pylori infection modifies the course of peptic disease is also reviewed. The clinical presentation of peptic diseases often differs in elderly people, and atypical symptoms are common. Accurate diagnosis requires aggressive endosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In their prospective study, Hilton et al demonstrated that only 30% of elderly patients with endoscopy proven PUD had typical epigastric pain [74]. Additionally, elderly patients with acute gastric or duodenal ulcer perforation might not exhibit classic signs of chemical peritonitis [75], which is partially due to hypochlorhydria observed in this age group. While medical treatment of PUD in elderly is not significantly different than in younger patients, medication side effects and interactions must be kept in mind.…”
Section: Stomachmentioning
confidence: 99%
“…In their prospective study, Hilton et al demonstrated that only 30% of elderly patients with endoscopy proven PUD had typical epigastric pain [74]. Additionally, elderly patients with acute gastric or duodenal ulcer perforation might not exhibit classic signs of chemical peritonitis [75], which is partially due to hypochlorhydria observed in this age group. While medical treatment of PUD in elderly is not significantly different than in younger patients, medication side effects and interactions must be kept in mind.…”
Section: Stomachmentioning
confidence: 99%
“…13,14 Age may also predispose to this disease by way of decreased defense mechanisms as a result of the natural physiologic changes of aging, such as decreased bicarbonate and prostaglandin secretion. 11,15 This latter is indeed concerning because 95 per cent of deaths related to this disease occur in patients over the age of 55. 12 Over the last three decades, decreases in rates for hospitalization, mortality (albeit only modestly), and even surgery have been noticed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been estimated that 20 per cent of all deaths in the United States are due to gastrointestinal disease, with up to 20 per cent of these caused by peptic ulcer disease. 11 Mortality for the two most common complications (perforation and bleeding) is reported to be at least 10 per cent. 12 Conventional management of PUD today has been greatly influenced by the 1982 incrimination of H. pylori as the prime causative agent.…”
Section: Discussionmentioning
confidence: 99%